Regional spillovers and spatial heterogeneity in matching workers and employers in Germany - Reinhold Kosfeld (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2006)
When job search takes place across labour markets, the standard flow approach to labour market analysis fails to uncover the effectiveness at which workers are matched to available jobs. A spatially augmented matching function is backed by a spatial search model with endogenous search intensity. Recent studies deal with the issue of spatial externalities by assuming the process of job matching to be homogenous across space. This study shows that this supposition is not valid for the unified Germany. Particularly differences in labour mobility give reason for the existence of West-East regimes of the matching process. Spatial heterogeneity is additionally found on the level of German macroregions. Though matching efficiency is affected by labour market characteristics, its cyclical pattern is closely related to business cycle fluctuations. Variation of regional mismatch over the business cycle can only explain a relatively small fraction of matching inefficiency.
Keywords: C21; C23; E24; J23; 330; Matching function; regional mismatch; spatial spillovers; spatial heterogeneity; Arbeitsmarkt; Angebot; Nachfrage; Räumliche Verteilung; Spillover-Effekt; Panel; Schätzung; Deutschland